Description Of Threat Perception Types To Chinese Ethnic Traders After The Burning Event Of 4 Viharas, 7 Temple And Social House In Tanjung Balai - Rizky Amelia Yasmin Siregar (Journal Basic Science and Technology, 2020)
This study aims to describe the type of threat perception felt by ethnic Chinese traders after the burning of 4 Vihara 7 Temples and Social Houses in Tanjungbalai. This study used a descriptive quantitative method with 550 research subjects with a scale built based on the type of threat perception in theory Intergroup Threat Theory (ITT) by Stephan (2009). The results of the analysis show that ethnic Chinese traders perceive the symbolic threat perception type more than the realistic threat perception type, this shows that ethnic Chinese traders do not feel a threat to their resources but rather threat to values, beliefs or morals.The implication of this research is that it can help ethnic Chinese traders to reduce the perception of threats against the non-Chinese ethnicity so as to make them feel more secure with their identity as ethnic Chinese and to worship at the temple or temple.